PENGARUH LINGKUNGAN TERHADAP PERILAKU MANUSIA: STUDI TERHADAP PERILAKU PENONTON BIOSKOP - Nuqul, Fathul Lubabin (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2005)
Human being always makes interaction with his environment. Both influence each other. The environment forces human to use certain behavior, and on the other hand human also influences the arrangement of environment. This influencing each other becomes vicious circle which happens in every element of human life, it does so in entertainment, in this case film or cinema. This research wants to see behavior of human being (moviegoer) linked with environmental settingThis research is conducted in the Movies Permata in Jogjakarta. The method of this research is qualitative. Data is taken from interview with seven informant and direct observation. The result of research, in general, indicates that pollution, temperature, setting of area, and also existence of others influences behavior of audience (moviegoer) in the building.Keywords: Environment, cinema, movies, and behavior.